Detailed analysis of the cell infiltrate and the expression of mediators of synovial inflammation and joint destruction in the synovium of patients with psoriatic arthritis: implications for treatment. Issue 12 (25th May 2006) - van Kuijk, A W R; Reinders-Blankert, P; Smeets, T J M; Dijkmans, B A C; Tak, P P
Abstract : Background: The synovial tissue is a primary target of many inflammatory arthropathies, including psoriatic arthritis (PsA). Identification of proinflammatory molecules in the synovium may help to identify potentially therapeutic targets. Objective: To investigate extensively the features of cell infiltration and expression of mediators of inflammation and joint destruction in the synovium of patients with PsA compared with patients with rheumatoid arthritis matched for disease duration and use of drugs. Methods: Multiple synovial tissue biopsy specimens were obtained by arthroscopy from an inflamed joint in 19 patients with PsA (eight oligoarthritis, 11 polyarthritis) and 24 patients with rheumatoid arthritis. Biopsy specimens were analysed by immunohistochemistry to detect T cells, plasma cells, fibroblast-like synoviocytes, macrophages, proinflammatory cytokines, matrix metalloproteinases and tissue inhibitor metalloproteinase-1, adhesion molecules and vascular markers. Stained sections were evaluated by digital image analysis. Results: The synovial infiltrate of patients with PsA and rheumatoid arthritis was comparable with regard to numbers of fibroblast-like synoviocytes and macrophages. T cell numbers were considerably lower in the synovium of patients with PsA. The number of plasma cells also tended to be lower in PsA. The expression of tumour necrosis factor alpha (TNFα), interleukin (IL) 1β, IL6 and IL18 was as high in PsA as in rheumatoid arthritis. The expression of matrix metalloproteinases, adhesion molecules and vascular markers was comparable for PsA and rheumatoid arthritis. Conclusion: These data show increased proinflammatory cytokine expression in PsA synovium, comparable to results obtained for rheumatoid arthritis, and support the notion that, in addition to TNFα blockade, there may be a rationale for treatments directed at IL1β, IL6 and IL18.